Circulating cytokines predict severity of rheumatic heart disease. (15th August 2019) - Diamantino Soares, Adriana C.; Araújo Passos, Lívia S.; Sable, Craig; Beaton, Andrea; Ribeiro, Victor Teatini; Gollob, Kenneth J.; Dutra, Walderez O.; Nunes, Maria Carmo P.
Abstract: Background: Rheumatic heart disease (RHD) is associated with inflammation that damages cardiac valves, often requiring surgical interventions. The underlying mechanisms involved in the disease progression are not completely understood. This study aimed to evaluate cytokine plasma levels in patients with RHD as possible markers of disease severity. Methods and results: Eighty-nine patients with RHD, age of 41 years ±11.5 years, were prospectively enrolled. RHD severity was defined as valve dysfunction that required invasive intervention, either valve repair or replacement. Peripheral blood samples were collected from all patients for cytokine measurements. The patients were followed up to look at adverse clinical events defined as either the need for valve intervention or death. At baseline, 64 (71.9%) patients had previously undergone valve intervention, whereas 25 patients had stable clinical presentation. Patients with severe RHD displayed higher levels of inflammatory cytokines than patients with stable disease. Cluster analysis showed segregation of severe and stable RHD based on IL-6/TNF-α and IL-6/IL-17A, respectively. IL-6 and TNF-α expression were positively correlated in severe but not in stable RHD patients. During a median follow-up of 23 months, 16 patients (18%) had an adverse outcome. IL-10 at baseline (HR 1.24, 95% CI 1.08–1.43, p = 0.003), and IL-4 (HR 1.12, 95% CI 1.01–1.24, p = 0.041) were predictors of events during the follow-up. Conclusions: High levels of cytokines are associated with severity of RHD. The co-regulated expression of IL-6 and TNF-α is associated with severe valve dysfunction, whereas high IL-10 and IL-4 levels predicted subsequently adverse outcome. Highlights: Inflammatory cytokines are associated with severity of rheumatic heart disease Cluster analysis showed segregation of severe rheumatic heart disease based on IL-6/TNF-α IL-6 and TNF-α expression were positively correlated in patients with severe but not in stable rheumatic heart disease. IL-10 and IL-4 measured at study enrollment were predictors of clinical events during the follow-up. This study provides the first evidence for the applicability of measuring circulating cytokines as a non-invasive strategy to detect biomarkers of rheumatic heart disease severity. Employing the analysis of circulating cytokines as markers of RHD severity provides a useful tool for risk stratification.